Measuring secondhand smoke in homes in Malaysia: a feasibility study comparing indoor fine particulate (PM2.5) concentrations following an educational feedback intervention to create smoke-free homes during the COVID-19 pandemic - Zulkifli, Aziemah; Abd Rani, Nurul Latiffah; Abdul Mutalib, Raisya Nur Syazmeen; Dobson, Ruaraidh; Engku Ibrahim, Tengku Azmina; Abd Latif, Norul Hernani; O’Donnell, Rachel; Uny, Isabelle; Zainal Abidin, Emilia; Semple, Sean (European Publishing, 2022)
Introduction: Extensive regulations have been introduced to reduce secondhand smoke (SHS) exposure among non-smokers in Malaysia. However, there is still a need to encourage behavior change of smokers in relation to making homes smoke-free. This feasibility study aimed to use low-cost air pollution monitors to quantify SHS concentrations in Malaysian households and to explore the practicality of using personalized feedback in educating families to make their homes smoke-free. Methods: A total of 35 smokers in three states in Malaysia were recruited via snowball and convenience sampling methods. Indoor fine particulate (PM2.5) concentrations in participants' homes were measured for 7 days before and after educational intervention using a pre-defined template, which included personalized air-quality feedback, and information on SHS impacts were given. The feedback was delivered over two 20-minute phone calls or in-person sessions following the completion of the air-quality measurements. Data were corrected for outdoor PM2.5 concentrations from the nearest environmental monitor. Results: Despite the challenges in conducting the project during COVID-19 pandemic, the delivery of the intervention was found to be feasible. Twenty-seven (77%) out of 35 participants completed PM2.5 measurements and received a complete intervention. The median (IQR: 25th -75th percentile concentrations) SHS-PM2.5 concentrations at baseline and follow-up were 18.3 µg/m3 (IQR: 13.3-28.3) and 16.2 µg/m3 (IQR: 10.4 - 25.6), respectively. There was a reduction of SHS-PM2.5 concentrations at follow-up measurement in the houses of 17 participants (63%). The change in corrected indoor PM2.5 concentrations between baseline and followup was not statistically significant (Z= -1.01, p=0.29). Conclusions: This educational intervention, combining the use of a low-cost air particle counter with personalized air-quality feedback, was found to be feasible in the Malaysian setting. It has potential to trigger behavior change among smokers, reducing indoor smoking and consequent SHS concentrations, and increasing smoke-free home implementation. A large-scale trial is needed.